Mixtec Sound Change Database 2.0: Integrating Tone Change - Sandra Auderset (Journal of Open Humanities Data)
This paper introduces and describes the second edition of the Mixtec Sound Change Database (Auderset & Campbell, 2024), which now includes a module on tone change. Tone change is an under-researched topic in historical linguistics and is virtually absent from cross-linguistic databases. The Mixtec languages from southern Mexico provide an ideal starting point for studies in this area, as they are all tonal and tone can be reconstructed to the proto-language. This updated version of the database thus serves as a model for including tonal data in synchronic and diachronic studies of languages and language families where this feature is present. This will support efforts towards a better understanding of suprasegmental change in Mixtec and beyond.